Assessment of the Factors Inhibiting Avitourism Growth in Arabuko Sokoke Forest in Kenya - Koki, J. N.; Pepela, A.; Wamukota, A.; Kidere, F. (Africa Environmental Review Journal, 2022)
Avitourism is currently one of the fastest growing sub sectors of ecotourism. In fact, it has the potential of contributing substantial income to the local economy in areas with high bird diversity. Arabuko Sokoke forest (ASF) is a promising bird life destination in Kenya with avitourism potential. However, its development and growth has not been achieved to the desired standards. This paper sought to assess factors that inhibit avitourism growth and development. Mixed research design was used were both quantitative and qualitative data were collected by use of a questionnaire and focus group discussion. The study sampled 353 respondents in four locations within Kilifi County and data was collected. The collected data was analyzed descriptively. About (26.0%) of the local community around Arabuko Sokoke forest are involved in avitourism activities thus contributing towards their livelihoods. However, major avitourism inhibitors in the study area included pollution and poor garbage and sewage disposal (69%), low support from government institutions (48%), corruption and embezzlement of local natural resources (62%) and low adoption and use of avitourism technologies (72%). Additionally, inadequacy of avitourism tools of trade, lack of avitourism policy, lack of requisite guiding trainings and disturbance of avitourism habitats were mentioned. Though Arabuko Sokoke has a potential, the development of avitourism activities and programs as well as avitourism policy to guide its growth and awareness campaign strategies should be initiated. This campaign should target and train the local community and other stakeholders on the value and importance of avitourism as an emerging high value form of tourism.